2020
DOI: 10.1515/jbcpp-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking study of flavonoid compounds for possible matrix metalloproteinase-13 inhibition

Abstract: ObjectivesMatrix metalloproteinase-13 (MMP-13) has been reported to be involved in different biological processes such as degradation of extracellular matrix proteins, activating or degrading some significant regulatory proteins, wound healing, tissue remodeling, cartilage degradation, bone development, bone mineralization, ossification, cell migration, and tumor cell invasion. Further, MMP-13 participates in many oral diseases such as tooth decay, gingivitis, and degradation of enamel and tissue around the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…They reported docking scores ranging between −8 and −10 Kcal/mol. In another study published by Taherkhani et al (2020) [56], isoquercetin and epicatechin showed respective scores of −8.96 and −6.4 Kcal/mol. These data are in perfect agreement with the results here obtained for isoquercetin and epicatechin.…”
Section: Hyperosidementioning
confidence: 85%
“…They reported docking scores ranging between −8 and −10 Kcal/mol. In another study published by Taherkhani et al (2020) [56], isoquercetin and epicatechin showed respective scores of −8.96 and −6.4 Kcal/mol. These data are in perfect agreement with the results here obtained for isoquercetin and epicatechin.…”
Section: Hyperosidementioning
confidence: 85%
“…erefore, it is suggested that targeting ECM-related genes may result in therapeutic effects in patients with ameloblastoma, although this needs confirmation in the future. Several flavonoids have shown inhibitory effects on MMP13 and MMP8 in previous studies [45,46]. However, the binding affinity of these natural compounds should be examined on other ECM-related genes such as MMP14.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth decay is one of the most common chronic diseases worldwide (32). It is a multifactorial disorder in which matrix metalloproteinases and S. mutans are most responsible for degrading the organic and mineral texture of the teeth, respectively (33,34). GTFase of S. mutans plays an essential role in biofilm formation, leading to more bacterial cohesion, acid production, and dental caries (11)(12)(13)35).…”
Section: Discussionmentioning
confidence: 99%
“…A pi-charge was detected between caffeic acid 3-glucoside and Asp588 (5.86 Å). It is worth mentioning that the π-π stack pairing, pi-charge, and salt bridges are the most stabilizing connections among ligands and proteins (33).…”
Section: Discussionmentioning
confidence: 99%